Brief Mindfulness Meditation Improves Emotion Processing - Wu, Ran; Liu, Lin-Lin; Zhu, Hong; Su, Wen-Jun; Cao, Zhi-Yong; Zhong, Shi-Yang; Liu, Xing-Hua; Jiang, Chun-Lei (Frontiers in Neuroscience, 2019)
Abstract Mindfulness-based interventions have previously been shown to have positive effects on psychological well-being. However, the time commitment, teacher shortage, and high cost of classic mindfulness interventions may have hindered efforts to spread the associated benefits to individuals in developing countries. Brief mindfulness meditation (BMM) has recently received attention as a way to disseminate the benefits of mindfulness-based interventions. Most existing BMM methods are adaptations of the classic approach. Few studies have investigated the mechanisms underlying the beneficial effects of BMM. We developed a 15-min BMM named JW2016, which is based on the core concepts of mindfulness, Anapanasati (breath meditation of Buddhist Vipassana), our practical experience, and the results of scientific reports on meditation. We investigated the effects of this BMM on mood and emotion processing in an effort to create an effective, convenient, safe, and standardized BMM method that could benefit individuals with limited time or money to devote to meditation. Forty-six healthy participants (aged 18–25 years) were randomly allocated to the BMM group (n = 23) or the emotional regulation education (ERE) control group (n = 23). Forty-two of the study participants cooperated fully in all measurements and interventions (one time daily for 7 consecutive days). Mood was measured with the Centre for Epidemiological Studies–Depression scale (CES-D) and the State Anxiety Inventory (SAI). Emotion processing was evaluated by assessing performance on an emotion intensity task, an emotional memory task, and an emotional dot-probe task. After intervention, the BMM group, but not the ERE group, showed a significant decreases in emotional intensity in response to positive as well as negative emotional stimuli, response time for emotional memory, and duration of attention bias toward negative emotional stimuli. Negative effects on mood state were found in the ERE group but not in the BMM group. This study demonstrated that BMM may improve aspects of emotion processing such as emotion intensity, emotional memory, and emotional attention bias. JW2016 BMM may be an effective, convenient, safe and standardized way to help practitioners remain focused and peaceful without any negative effect on emotion.